Pressure effects on iron-based superconductor CaFe0.88Co0.12AsF. (29th May 2019) - Huang, J; Zhang, C; Ma, Y H; Wang, T; Mu, G; Yu, L; Hu, T; Xiao, H
Abstract: Systematic measurements of electrical resistivity and Hall coefficient under high pressure were performed on CaFe0.88 Co0.12 AsF single crystal samples. The superconductivity is suppressed quickly by pressure and can not be detected down to 2 K at above 12.7 GPa, while the magnitude of the Hall coefficient shows a very weak pressure and temperature dependence. A comprehensive analysis considering the pressure dependence of, , residual resistivity ratio, and the Fermi-liquid term of the resistivity indicates that the electron correlation is an important factor in superconductivity of iron-based superconductors.